prepdat- An R Package for Preparing Experimental Data for Statistical Analysis - Allon, Ayala S.; Luria, Roy (Journal of open research software, 2016)
In many research fields the outcome of running an experiment is a raw data file for each subject, containing a table in which each row describes one trial conducted during the experiment. The next step is to merge all files into one big table, and then aggregate it into one finalized table in which each row corresponds (usually) to the averaged performance of each subject. prepdat- An R package- enables to easily perform these steps, including several possibilities for dependent measures and trimming procedures. prepdat helps researchers to optimize and speedup their analysis, and to better understand the results. Keywords: R, Data manipulation, Data aggregation, Data analysis, Trimming procedures, Experimental designs